Peran Keluarga dan Pendidikan Terhadap Anak Berkebutuhan Khusus: Analisis Tunawicara dan Tunadaksa pada Niatus Shalilah di Podcast Denny Sumargo - Br Nainggolan, Debora Putriani; Sihite, Visensia; Angelia Gracia Ginting; Aditia Elovani Keliat; Anisa May Sarah Manalu; Dear Ezra Sipayung; Anggia Puteri (Indo-MathEdu Intellectuals Journal, 2025)
Education is a fundamental right for every individual, including Children with Special Needs (CSN) such as speech-impaired and physically disabled children. This study employs a qualitative descriptive method to analyze the role of family and education in supporting CSN, based on narratives from Denny Sumargo’s podcast. Data collection techniques include observation, transcription, and literature review. The findings reveal that the family plays a crucial role in building self-confidence, providing emotional support, and ensuring equitable access to education for CSN. Additionally, an adaptive inclusive education system contributes significantly to the optimal development of CSN. These findings emphasize the importance of synergy between families and educational institutions in creating a supportive environment for CSN